ACCOUNTING-ANALYTICAL PROVIDING OF RIZIK-MANAGEMENT IN THE SUSTAINABLE DEVELOPMENT OF COMPANIES - Tarasova, T. O.; Cherchata, A. O.; Staverska, T. O. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
The methodological aspects of accounting and analytical support with the informational support of situational, process, integrated and continuous risk management in the conditions of sustainable development on the basis of the concept of business continuity have been determined, which allowed to determine criteria of risks acceptance on the basis of professional judgements. Detailed qualitative and quantitative managed parameters of diagnostics and monitoring of specific business processes that characterize the trading industry in the process of managing sustainable development under the influence of crises are the milestones of its goal setting and functioning. Based on the "Neo-Systematic" approach, Steakholder’s concept and process approach of the American Quality Association it has been proved that the target paradigm of sustainable development should have a hybrid character, combining heterogeneous theoretical approaches to the management of business continuity. The main indicators of the threats of continuity of activity covering the main segments of the business of the enterprise are defined: consumer segments, price offers, sales channels, customer relations, cash flows, property resources. The newest paradigm of risk management is proposed to be formed in the form of a system of empirical knowledge, built on the principles of objective reality (in the form of facts of economic life) and the theoretical basis (in the form of principles, assumptions, laws, concepts). This approach allows monitoring in the framework of continuous risk management in the system of early detection of problems that arise when ensuring the continuity of the enterprise. The accounting and analytical support formed in the framework of the latest risk management paradigm can be considered as a system of purposeful influence on all types of risk, which allows to minimize the consequences of changes in economic conditions and investment climate, to identify problems in financial flows. Proceeding from this, a model of risk management support in the system of accounting and analytical support is proposed based on the concept of business continuity.